Carrying Capacity Analysis of Batu Belimbing Nature Tourism in East Singkawang District Singkawang City West Kalimantan - Slamet Rifanjani; Viona Aprinanda Ahie; Muflihati Muflihati; Marwanto Marwanto (Jurnal Ilmu Lingkungan, 2024)
Batu Belimbing Natural Tourism (BBNT) is located in Nyarumkop Village, East Singkawang District, Singkawang City, and is one of the natural tourist attractions that has the potential to be developed. The number of visitors continues to increase, but the carrying capacity of the tourist area is still unknown. The carrying capacity value of BBNT needs to be analyzed to determine its ability to remain sustainable and accommodate visitors optimally so that visitor satisfaction can be achieved without environmental damage. The purpose of this research is to analyze the carrying capacity of BBNT as a natural tourist attraction based on three factors: physical (PCC), real (RCC), and effective (ECC) carrying capacity. This research used observation and interview methods. Qualitative descriptive analysis was used in this research. The calculation results show that the PCC value is 5,211 people/day, the RCC value is 1,637 people/day, and the ECC value is 1,637 people/day. The carrying capacity value of BBNT has the equation PCC > RCC = ECC; this means that the carrying capacity of BBNT is large and can still accommodate its visitors with all activities if its RCC and ECC values are lower than its PCC value (5,211 people/day).